2020
DOI: 10.1016/j.jcv.2020.104570
|View full text |Cite
|
Sign up to set email alerts
|

Pooling of SARS-CoV-2 samples to increase molecular testing throughput

Abstract: Highlights Four-way pooling correctly identified SARS-CoV-2 in 94 % of positive samples (n = 30/32) tested. Low viral loads, corresponding with late C T s, may be missed by the pooling process. 1:4 pooling is associated with expected 2 C T loss in analytical sensitivity. All individually negative samples (n = 128) were also negative by 4-way pooling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(58 citation statements)
references
References 18 publications
10
48
0
Order By: Relevance
“…Lohse et al, (13) could be consistently identified when the N-gene Ct value of the Individual sample making up the pool was <35 for pools of 5 and <31 for pools of 10. These results are consistent with those of another study (17) and suggest that smaller pool sizes will help in improving sensitivity of detection.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Lohse et al, (13) could be consistently identified when the N-gene Ct value of the Individual sample making up the pool was <35 for pools of 5 and <31 for pools of 10. These results are consistent with those of another study (17) and suggest that smaller pool sizes will help in improving sensitivity of detection.…”
Section: Discussionsupporting
confidence: 91%
“…Several pooling strategies and PCR protocols have been studied for COVID-19 diagnosis (13,14,17,18). In most studies, samples were pooled before RNA extraction, however, pooling of extracted RNA has also been reported for COVID-19 testing (15,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pool testing has gained importance to fight the COVID-19 pandemic, as challenges involving cost and logistics are at the core of shared struggles to promote large-scale screenings worldwide 10 . Traditional pooling methods proposed 9-15 rely on the combination of multiple individual samples prior to RNA extraction or RT-qPCR, leading to a dilution factor directly related to the number of samples in the pool 9,[11][12][13][14][15] . This dilution effect has been of major concern over the diagnostic performance of pool testing procedures 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The detection of the positive samples with low viral load was not feasible by pooling. On the other hand, all the samples which individually determined as negative, were also negative when tested in pools ( Perchetti et al, 2020b ).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%